2D-nanomaterials for AKI treatment - Chen, Qiaohui; Wang, Xiaoyuan; Yuan, Chao; Nan, Yayun; Huang, Qiong; Ai, Kelong (Frontiers in Bioengineering and Biotechnology, 2023)
Acute kidney injury (AKI) has always been considered a sword of Damocles over hospitalized patients and has received increasing attention due to its high morbidity, mortality, and poor prognosis. Hence, AKI shows a serious detrimental impact not only on the patients themselves but also on the whole society and the associated insurance system. Redox imbalance caused by bursts of reactive oxygen species (ROS) at the renal tubules is key to the structural and functional impairment of the kidney during AKI. Unfortunately, the failure of conventional antioxidant drugs has led to a halt in the clinical management of AKI, which is limited to mild supportive therapies. Nanotechnology-mediated antioxidant therapy represents a promising therapeutic strategy for AKI. In recent years, 2D nanomaterials, a new subtype of nanomaterials with ultra-thin layer structure topology, have demonstrated significant advantages in AKI therapy due to their ultrathin structure, large specific surface area and unique kidney targeting. Herein, we reviewed the recent progress of various 2D nanomaterials including DNA origami, germanene, and MXene for AKI therapy, and discussed their current opportunities and future challenges, aiming to provide new insights and theoretical support for the development of novel 2D nanomaterials and AKI treatment.